Design and Implementation of a Teaching Assistant Information System Using Laravel Filament and Extreme Programming - Nasrul; Edi Wibowo; David Wahyu Wismanindra (Program Studi Ilmu Komputer, Universitas Pakuan, 2026)
The management of teaching assistants at Sekolah Tinggi Teknologi Terpadu Nurul Fikri (STT-NF) has traditionally been conducted using manual processes, resulting in time inefficiencies, data inaccuracies, and limited integration of information. To address these challenges, a web-based Teaching Assistant Information System was developed using the Laravel Framework with Filament as the administrative interface and PostgreSQL as the database management system. The system is designed to streamline teaching assistant recruitment, class and assistant scheduling, and honorarium calculation in a structured and efficient manner. The development process applies the Extreme Programming (XP) methodology, which emphasizes iterative development, intensive user involvement, and adaptability to changing requirements. The results indicate that the proposed system improves efficiency and data accuracy while supporting administrative and academic staff in monitoring activities and making informed decisions.